Obtaining Academic Employment Within the U.S. Context: The Experiences of Strugglers - Binh Chi Bui; Elsa Maria Gonzalez (MDPI AG, 2024)
In the present study, we explored the experiences of Ph.D. graduates in navigating the U.S. academic job market. We used interpretative phenomenology and interview data from 15 Ph.D. graduates. These participants came from different racial/ethnic backgrounds and were either U.S. citizens or international candidates while pursuing their current academic positions. Our findings reveal that during their job search, the participants, especially racially minoritized individuals and immigrants, faced concerns about the best-fit qualities, negotiated their failures with a flexible mindset, and introspected to restore their academic identity. These findings suggest the internal struggles of academic job seekers and the complexities of validating doctoral employability in a highly competitive environment. Strong agency to overcome these challenges is essential to any successful academic job seekers. Given the findings, the study emphasizes the need to further research and enhance the employability of Ph.D. graduates in today's academic landscape.